2016
DOI: 10.1016/j.tibs.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The APOBEC Protein Family: United by Structure, Divergent in Function

Abstract: Summary The APOBEC (Apolipoprotein B mRNA Editing Catalytic Polypeptide-like) family of proteins has diverse and important functions in human health and disease. These proteins have an intrinsic ability to bind to both RNA and single-stranded (ss)DNA. Both function and tissue-specific expression varies widely for each APOBEC protein. We are beginning to understand that the activity of APOBEC proteins is regulated through genetic alterations, changes in their transcription and mRNA processing, and through their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
360
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(373 citation statements)
references
References 144 publications
(189 reference statements)
9
360
1
3
Order By: Relevance
“…APOBEC and AID enzymes modify cytidine in either mRNA or single-stranded (ss) DNA to form uracil [5][6][7]. Other members have also been identified, including APOBEC2 and APOBEC4, though they do not have demonstrated catalytic activity [3,8,9].…”
Section: Apobec Family Of Enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…APOBEC and AID enzymes modify cytidine in either mRNA or single-stranded (ss) DNA to form uracil [5][6][7]. Other members have also been identified, including APOBEC2 and APOBEC4, though they do not have demonstrated catalytic activity [3,8,9].…”
Section: Apobec Family Of Enzymesmentioning
confidence: 99%
“…In RNA, where uracil has a coding function, deamination is an RNA editing tool. In DNA, the formation of uracil by APOBEC/AID is a promutagenic lesion which in some cases can be detrimental and cause cancer, but in other cases enables evolution of antibody genes and inactivation of viruses, retroelement, or other cytoplasmic inflammation-inducing DNA [5,11,12].…”
Section: Apobec Family Of Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…20,34,[39][40][41][42][43] These studies have concluded that A3B prefers DNA substrates but can bind and catalyze other substrates with significantly lower activity. 44 DNA and RNA differ in structure by only one hydroxyl group (at the C2' position), which is enough to change the backbone sugar ring pucker from C2' endo (for DNA) to C3' endo (for RNA). It is suspected that this difference in conformational preference is a contributing factor for A3B's selectivity for DNA over RNA, but the exact mechanism is not known.…”
Section: Introductionmentioning
confidence: 99%